Bagaimana Peran Self-Compassion dan Dukungan Sosial terhadap Kecenderungan Depresi pada Pasien Rehabilitasi Narkoba? - Wahyuningrat, Febryliana Dewi; Puspitasari, Devi; Lestari, Bawinda Sri (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2023)
This study aims to look at the role of self-compassion and social support together in the tendency to depression in drug rehabilitation patients. The participants of this study were 46 drug rehabilitation patients in the city of Surabaya. Research data collection was obtained by physically distributing questionnaires to drug rehabilitation patients. The analysis technique uses multiple regression analysis with the help of Statistical Package for the Social Science (SPSS) version 25 for Windows. The results showed that there was a negative and significant effect of self-compassion on depression tendencies in drug rehabilitation patients. Meanwhile, support does not have a significant effect on the tendency of depression in drug rehabilitation patients. The effective contribution of self-compassion and social support to depression tendencies in drug rehabilitation patients is 33.1%. Penelitian ini bertujuan untuk melihat peran self-compassion dan dukungan sosial secara bersama-sama terhadap kecenderungan depresi pada pasien rehabilitasi narkoba. Partisipan penelitian ini adalah pasien rehabilitasi narkoba di Kota Surabaya sejumlah 46 orang. Pengambilan data penelitian diperoleh dengan cara menyebarkan kuesioner secara fisik pada pasien rehabilitasi narkoba. Teknik analisis menggunakan analisis regresi berganda dengan bantuan Statistical Package for the Social Science (SPSS) versi 25 for Windows. Hasil penelitian menunjukkan bahwa terdapat pengaruh negatif dan signifikan antara self-compassion terhadap kecenderungan depresi pada pasien rehabilitasi narkoba. Sedangkan dukungan tidak memiliki pengaruh signifikan terhadap kecenderungan depresi pasien rehabilitasi narkoba. Adapun sumbangan efektif self-compassion dan dukungan sosial terhadap kecenderungan depresi pada pasien rehabilitasi narkoba adalah sebesar 33,1%.